Behavior of Short Columns Reinforced with Welded Wire Fabric as Transverse Reinforcement under Concentric Loading - LEELATANON, Satjapan; ARAMRAKS, Trakool (Walailak Journal of Science and Technology (WJST), 2011)
The purpose of this study was to investigate the behavior of concrete columns reinforced by Welded Wire Fabric, WWF, as transverse reinforcement under concentric loading and to compare the results with concrete columns reinforced by round bar as tie reinforcement when the volumetric ratio of transverse reinforcement was equal. Additionally, the effect of the spacing of transverse tie reinforcement on strength and ductility of the columns was studied by testing six different types of column specimens. The results indicated that the strength of the column increased slightly when the volumetric ratio was increased. The ductility of the column also had the same trend as the strength. However, the comparison of ductility showed columns reinforced by WWF tie had ductility indexes less than columns reinforced by RB 6 tie bars. This was because the WWF welded joint broke when subjected to lateral pressure from the concrete core, while conventional RB 6 tie showed ductile behavior due to the hook being stretched. Moreover, the test results were compared with the constitutive models proposed by Saatcioglu and Chan. The results showed that Saatcioglu’s formula is more practical than Chan’s formula for confined concrete columns. However, the mode of failure of transverse reinforcements that affects the ductility of the column should be considered.